Improving the quality of design calculations of viscous flow in low-flow centrifugal compressor stages by methods of computational fluid dynamics through reasonable application of different turbulence models - S. V. Kartashev; Yu. V. Kozhukhov (Омский научный вестник)
The paper considers the issue of improving the quality of the numerical experiment in the calculation of viscous gas in the flowing part of a low-flow centrifugal compressor stage. The choice of turbulence model in creating a calculation model for calculations by methods of computational fluid dynamics is substantiated. As object of research is chosen low-flow stage with conditional flow coefficient Ф=0,008 and relative width at impeller outlet b2 /D2 =0,0133. The issue of qualitative modeling of friction losses in low-flow stages is of fundamental importance and is directly related to the choice of turbulence model. It is shown that the choice of low-Reynolds turbulence models in the case of unloaded and discontinuous low-flow stages can be made from the main common models (SpalartAllmaras, SST, k-ω) based on the economy of calculations, speed of convergence, solution stability and adequacy of the obtained results. For models with wall functions, the quality of the mesh model and the observance of the dimensionless distance to the wall y+ throughout the calculation domain are particularly important. For highReynolds turbulence models, at values of y+=25...50 on all friction surfaces of the computational domain in the optimal mode of operation, the grid independence of the solution for the entire gas-dynamic characteristic is ensured. It is unacceptable for y+ to fall into the transition region of 4...15 between the viscous sublayer and the region of the logarithmic velocity profile.